Oseltamivir induced sinus bradycardia: an area of potential concern - Shah, Karan B.; Shah, Bhavesh S.; Malhotra, Supriya D.; Patel, Pankaj R. (International Journal of Basic & Clinical Pharmacology, 2018)
Oseltamivir was approved for the prevention and treatment of influenza in 1999 by the USFDA (US Food and Drug Administration). The use of Oseltamivir is increasing rapidly all over the world, especially after the 2009 “Swine Flu” pandemic. Less data is published as far as the cardiovascular side effects of Oseltamivir are concerned, but it could be associated with some serious cardiovascular side effects. This study presented a case series of 5 cases suspected to be suffering from seasonal influenza H1N1 (“Swine Flu”), who developed sinus bradycardia while they were on Oseltamivir therapy.